2021
DOI: 10.3390/ijms22147602
|View full text |Cite
|
Sign up to set email alerts
|

The Structural Effect of FLT3 Mutations at 835th Position and Their Interaction with Acute Myeloid Leukemia Inhibitors: In Silico Approach

Abstract: FMS-like tyrosine kinase 3 (FLT3) gene mutations have been found in more than one-third of Acute Myeloid Leukemia (AML) cases. The most common point mutation in FLT3 occurs at the 835th residue (D835A/E/F/G/H/I/N/V/Y), in the activation loop region. The D835 residue is critical in maintaining FLT3 inactive conformation; these mutations might influence the interaction with clinically approved AML inhibitors used to treat the AML. The molecular mechanism of each of these mutations and their interactions with AML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 74 publications
0
9
0
Order By: Relevance
“…In wild-type FLT3, D835 may stabilize the autoinhibited state by forming interactions with the α-helix, including S838 residue [26]. Mutations at this position lead to increased phosphorylation probably through the destabilization of the autoinhibited conformation [20,27]. A similar mechanism explains the activating nature of the equivalent mutations (D816V/H) in c-KIT receptor [28].…”
Section: A Novel Mutation Of Fgfr1 (D647) Recurs In the Kinase Domain...mentioning
confidence: 97%
“…In wild-type FLT3, D835 may stabilize the autoinhibited state by forming interactions with the α-helix, including S838 residue [26]. Mutations at this position lead to increased phosphorylation probably through the destabilization of the autoinhibited conformation [20,27]. A similar mechanism explains the activating nature of the equivalent mutations (D816V/H) in c-KIT receptor [28].…”
Section: A Novel Mutation Of Fgfr1 (D647) Recurs In the Kinase Domain...mentioning
confidence: 97%
“…It was found that the mutation (D8G, S104R and C138Y) in PncA was responsible for rigid binding cavity which in turn abolished conversion of pyrazinamide to its active form and was the reason for pyrazinamide resistance [19]. Similarly, docking and molecular dynamics simulation techniques have been used to study other diseases as well [20][21][22][23]. In the current scenario, artificial intelligence based technologies have started to enter the field of antibiotic design.…”
Section: Introductionmentioning
confidence: 99%
“…This study aims at identifying the pathogenicity of such missense mutations using bioinformatics-based approaches. Recent advances in bioinformatics have aided in understanding the fundamentals of genetic makeup, such as the functional impact of amino acid residues on the function and structure of the protein. These reported deleterious mutations may have a significant impact on the protein’s function. Therefore, it is crucial to identify the pathogenicity of mutations identified in the RAD class of proteins.…”
Section: Introductionmentioning
confidence: 99%